Letter - North Staffs. Trades and Labour Council, n.d. (Stoke-on-Trent)
1926-05-04 "Letter - North Staffs. Trades and Labour Council, n.d." [g0396001.jpg], 4 May 1926, North Staffs. Trades and Labour Council Local Organisation